Conceptualizing "the end" of COVID-19: temporality and linear mobilization toward health. Issue 2 (3rd April 2022) - Tabrizi, Hannah; Levina, Marina
ABSTRACT: COVID-19 has crystalized how Western sociopolitical, cultural, and biomedical understandings of health advance the spaciotemporal logic of "the end." This logic defines health in terms of linear accessibility to cures while ignoring the intersectional mechanisms of systemic inequality. Such logics stress an individual's ability to mobilize along the timeline of health, ignoring the stoppages shaped by race, class, ability, and gender. This effectively casts public health as a matter of managing individual choice without attending to systems of power. The logic of "the end" works in tandem with the metaphors of "darkness" and "light." Within the context of COVID-19, these metaphors demarcate health as a universally attainable good defined by Western medicine, whiteness, and normative ability. This temporal logic of the pandemic crystalizes how whiteness and ability shape notions of health in ways that render precariously situated bodies immobile and essentially ill.